Basic electronics for tomorrow's inventors - Dossis, Nick. (New York : McGraw-Hill, 2013)
"Learn all about electronics with fun experiments and projects"--
"A Thames & Kosmos book."
Includes index.
Keywords: Electronics -- Experiments; Electricity -- Experiments; Electricity -- Experiments; Electronics -- Experiments